The Distributional Effects of Government Spending Shocks in Developing Economies - Furceri, Davide (IMF Working Papers; Working Paper ;, 2018)
We construct unanticipated government spending shocks for 103 developing countries from 1990 to 2015 and study their effects on income distribution. We find that unanticipated fiscal consolidations lead to a long-lasting increase in income inequality, while fiscal expansions lower inequality. The results are robust to several measures of income distribution and size of the fiscal shocks, to an alternative identification strategy, across expansions and recessions and across country groups (low-income countries versus emerging markets). An additional contribution of the paper is the computation of the medium-term inequality multiplier. This is on average about 1 in our sample, meaning that a cumulative decrease in government spending of 1 percent of GDP over 5 years is associated with a cumulative increase in the Gini coefficient over the same period of about 1 percentage point. The multiplier is larger for total government expenditure than for public investment and consumption (with the former having larger effect), likely due to the redistributive role of transfers. Finally, we find that (unanticipated) fiscal consolidations lead to an increase in poverty.